Metastatic gastric adenocarcinoma in a pregnant woman - Büyükavcı, Raikan; Apaydın, Hakan; Aktürk, Semra (The European Research Journal, 2018)
Gastric cancers occur in only 0.025% to 0.1% of all pregnancies. We present a pregnant woman with gastric adenocarcinoma associated with bone metastasis. She is 36-year-old (gravida:4, para:0) 16-week pregnancy, complaining of nausea, vomiting, weight loss (~15 kg) and low back pain. Although the patient considered the condition to be related with pregnancy and underestimated its importance. She had high erythrocyte sedimentation rate (107 mm/h) and anemia (hemoglobin = 9.4 gr/dl). Lumbar magnetic resonance imaging showed L4 vertebrae malign compression fracture and diffuse bone metastasis. Because of the patient's melena, esophagogastroduodenoscopy was performed and biopsy result was reported as stomach adenocarcinoma. It is important to evaluate the symptoms of low back pain and pregnancy related symptoms carefully and do not cause delays in diagnosis due to overlapping symptoms.